Review for cost-effectiveness analysis of laparoscopic Intra-peritoneal Onlay Mesh for ventral hernia repair in Indian settings - Charu Guleria; Dinesh Kumar; Krushna Chandra Sahoo (Cost Effectiveness and Resource Allocation)
Abstract Background Health Technology Assessment in India (HTAIn) carries evidence-based decision making in improving health care. This study was done to assess cost-effectiveness of the laparoscopic IPOM technique compared to open VHR from health system perspective of India. Methods A Meta-analysis of outcomes of both procedures was carried out whereas cost estimates were obtained from national health system costing database. Results A meta-analysis of Randomized Control Trials (RCTs) showed similar risk in hernia recurrence rates between laparoscopic IPOM and open technique (RR: 1.28 95% C.I: 0.81, 2.04) but with significantly less risk for wound infections (RR: 0.31 95% C.I: 0.18, 0.54). Estimated cost from National Health System Costing Database (NHSCD) per VHR was high for laparoscopic IPOM (INR 58,872) compared to open hernioplasty (INR 36,166) with estimated Incremental Cost-Effective Ratio of INR 5,023 per wound infection averted. Conclusions Laparoscopic IPOM was not clinically effective in hernia recurrence and less likely to be cost-effective